Competing over the "left behind": the effect of independent local lists on the electoral performance of populist parties - Eliska Drapalova; Fred Paxton (Political Research Exchange, 2025)
Rising dissatisfaction with established politics has driven widespread partisan dealignment, weakening mainstream parties and fuelling the ascent of populist challengers. Yet alongside populist parties, another group has gained traction across Europe: independent local lists (ILLs). These locally organised groups present themselves as alternatives to party politics and may channel anti-establishment sentiment. This paper investigates how the rise of ILLs affects the performance of populist parties –particulary in so-called `left behind' places – and how this relationship varies across populist parties of different ideological types. The analysis draws on an original dataset of local elections in 670 municipalities over four electoral rounds in the Czech Republic, a country in which both populist parties and ILLs have recently emerged and now play prominent roles. Fixed-effects panel models show that the presence of ILLs significantly impedes the electoral performance of populist parties, including in economically deprived contexts. These findings shed new light on the conditions under which local political actors are able to constrain the development of populist parties, offering broader insights into strategic responses to voter grievances and the rising demand for anti-establishment politics.
Keywords: 300; Local politics; populist parties; electoral competition; panel data; Czech Republic